EFFECTIVENESS OF HORIZONTAL PEER-ASSISTED LEARNING IN PHYSICAL EXAMINATION PERFORMANCE - Shah, Inamullah; Mahboob, Usman; Shah, Sajida (Journal of Ayub Medical College Abbottabad, 2017)
Background: All students cannot be individually trained in physical examination skills due to faculty and time limitations. Peer-assisted learning (PAL) can solve this dilemma if it is used in undergraduate curriculum. Empirical effectiveness of horizontal peer-assisted learning model has not been reported previously. The objective of this study was to compare horizontal peer-assisted learning (PAL) with expert-assisted learning (EAL) in teaching of physical examination skills. Methods: This is a randomized controlled study (Solomon four group design) carried out at a medical school. A total of 120 undergraduate year 5 students were randomized into two groups to undergo training in four areas of physical examination. Stratified random sampling technique was used. Group 1 was trained by EAL while Group 2 by PAL. Half students from both groups were given a pre-test to assess the testing effect. Both groups were given a post-test in the form of an OSCE. Independent samples t-test and paired sample t-test were used as tests of significance. Results: Group 2 scored significantly higher than Group 1. There was significant difference (p=.000) in mean post-test scores of Group-1 (69.98±5.6) and Group-2 (85.27±5.6). Difference in mean scores was not significant (p=.977) between students who had taken the pre-test and those who had not. Conclusion: This study has implications in curriculum development as it provides quantitative evidence indicating that horizontal PAL as a learning strategy can actually replace, rather than augment, expert-assisted learning in teaching clinical skills to undergraduate students. Keywords: Clinical education; horizontal PAL; Peer-assisted learning; Quantitative; Assessment; Randomized controlled trial; Solomon’s four group design